Critical roles of astrocytic‐CCL2‐dependent monocyte infiltration in a DJ‐1 knockout mouse model of delayed brain repair. Issue 10 (16th March 2020) - Choi, Dong‐Joo; Yang, Hajie; Gaire, Sushil; Lee, Keon Ah; An, Jiawei; Kim, Byung Gon; Jou, Ilo; Park, Sang Myun; Joe, Eun‐Hye
Abstract: Monocyte‐derived macrophages play a role in the repair of the injured brain. We previously reported that a deficiency of the Parkinson's disease (PD)‐associated gene DJ‐1 delays repair of brain injury produced by stereotaxic injection of ATP, a component of damage‐associated molecular patterns. Here, we show that a DJ‐1 deficiency attenuates monocyte infiltration into the damaged brain owing to a decrease in C‐C motif chemokine ligand 2 (CCL2) expression in astrocytes. Like DJ‐1‐knockout (KO) mice, CCL2 receptor (CCR2)‐KO mice showed defects in monocyte infiltration and delayed recovery of brain injury, as determined by 9.4 T magnetic resonance imaging analysis and immunostaining for tyrosine hydroxylase and glial fibrillary acid protein. Notably, transcriptome analyses showed that genes related to regeneration and synapse formation were similarly downregulated in injured brains of DJ‐1‐KO and CCR2‐KO mice compared with the injured wild‐type brain. These results indicate that defective astrogliosis in DJ‐1‐KO mice is associated with decreased CCL2 expression and attenuated monocyte infiltration, resulting in delayed repair of brain injury. Thus, delayed repair of brain injury could contribute to the development of PD. Main Points: A DJ‐1 deficiency attenuates infiltration of monocytes owing to a decrease in CCL2 expression in astrocytes, which in turn led to delay in repair of brain injury. Abstract : A DJ‐1 deficiency attenuates infiltration of monocytes owing to a decrease in CCL2 expression in astrocytes, which in turn led to delay in repair of brain injury.